A nationwide participatory programme to measure person‐centred hospital care in Italy: Results and implications for continuous improvement. (20th May 2021) - Cardinali, Flavia; Carzaniga, Sara; Duranti, Giorgia; Labella, Barbara; Lamanna, Alessandro; Cerilli, Micaela; Caracci, Giovanni; Carinci, Fabrizio
Abstract: Background: Patient‐centredness has been targeted by the Italian government as a key theme for the future development of health services. Objective: Measuring patient‐centred health services in partnership with citizens, health professionals and decision makers. Design: National participatory survey in a large test set of hospitals at national level. Setting and participants: A total of 387 hospital visits conducted in 16 Italian regions by over 1, 500 citizens and health professionals during 2017‐2018. Main variables and outcome measures: An ad hoc checklist was used to assess person‐centredness in hospital care through 243 items, grouped in 4 main areas, 12 sub‐areas and 29 person‐centred criteria (scored 0‐10). GEE linear multivariate regression was used to explore the relation between hospital characteristics and person‐centredness. Results: Person‐centred scores were moderately high, with substantial variation overall (median score: 7.0, range: 3.2‐9.5) and by area (Care Processes: 6.8, 2.0‐9.8; Access: 7.4, 2.7‐9.7; Transparency: 6.7, 3.4‐9.5 and Relationship: 7.3, 0.8‐10.0). Multivariate regression found higher scores for increasing volumes of activity (quartile increase: +0.21; 95% CI: 0.13, 0.29) and lower scores in the south and islands (−1.03; −1.62, ‐0.45). Discussion: The checklist has been applied successfully by over 1, 500 collaborators who assessed hospitals in 16 distinct Regions and Autonomous Provinces of Italy. Despite an overall positive mark, all scores were highly variable by location and hospital characteristics. Conclusion and patient or public contribution: A national participatory programme to improve patient‐centredness in Italian hospitals highlighted critical areas with the direct input of citizens.